A multi-proxy approach for reconstructing oceanographic dynamics during the Holocene Development and Application of benthic foraminifera as proxies in the Polar North Atlantic - Skirbekk, Kari (UiT Norges arktiske universitet, 2014)
The papers of this thesis is not available in Munin: I: Skirbekk, Kari; Klitgaard-Kristensen, Dorthe; Rasmussen, Tine Lander; Koc, Nalan; Forwick, Matthias: 'Holocene climate variations at the entrance to a warm Arctic fjord: evidence from Kongsfjorden Trough, Svalbard'. Geological Society Special Publication 2010; Volume 344: 289-304. Available at http://dx.doi.org/10.1144/SP344.20 II: Skirbekk, Kari; Hald, Morten; Marchitto, Thomas; Junttila, Juho; Klitgaard Kristensen, Dorthe: ‘Mg/Ca thermometry in an Arctic setting: temperature calibrations for three species of benthic foraminifera and implications on seasonality’. (Manuscript) III: Skirbekk, Kari; Hald, Morten; Husum, Katrine; Junttila, Juho: ‘Oceanographic development the last 1700 years along the Atlantic Water – Arctic Water boundary in the Polar North Atlantic, inferred from bottom water temperature and salinity’. (Manuscript) IV: Rasmussen, Tine Lander; Thomsen, Erik; Skirbekk, Kari; Slubowska-Woldengen, Marta; Klitgaard Kristensen, Dorthe; Koc, Nalan: ‘Spatial and temporal distribution of Holocene temperature maxima in the northern Nordic seas: interplay of Atlantic-, Arctic- and polar water masses’. Quaternary Science Reviews 2013; Volume 92: 280-291. Available at http://dx.doi.org/10.1016/j.quascirev.2013.10.034 Two sediment cores and several sediment surface samples have been retrieved in order to develop and apply benthic foraminifera as proxies in the Polar North Atlantic. The purpose of the surface samples was to develop the Mg/Ca method for cold water environments, as this has been proven a valuable paleo-thermometer for several marine environments. This was done for three species of Benthic foraminifera: I. helenae/norcrossi, B. frigida and N. labradorica. A mayor finding in this process was that the different species has deviating calcifying season. This implied that seasonal signals could possibly be reconstructed in paleo-records. By using these and faunal assemblages of benthic foraminifera, the two sediment cores from Kongsfjorden, ...